Performance of winter season intercrops in gum-arabic based agroforestry system in Bundelkhand region of Central India - Prasad, Rajendra; Singh, R.; Handa, A.K.; Alam, B.; Shukla, Ashok; Singh, Prashant; Tripathi, V.D. (Indian Journal of Agroforestry, 2020)
Present study was carried out in an agri-horti-silviculture model, established during 2009 under an ICAR sponsored network project â€œHarvesting, Processing and Value Addition of Natural Resins and Gumsâ€. The model comprised of a gum-yielding plant species (Acacia senegal) and three horticulture plant species (Citrus limon, Aegle marmelos and Carissa carandas). A. senegal, A. marmelos and C. limon were planted at different spacings in rows while C. carandas was planted on boundaries (three sides). In the model, intercropping commenced in winter season of 2012-13. Brassica campestris (var. Varuna) was grown during 2012-13 & 2013-14 and Triticum aestivum (var. HUW 234 Z-1) during 2014-15 & 2015-16. During study period, survival of A. senegal ranged from 86-100%, C. limon from 83-96%, A. marmelos from 71-96% and C. carandas up to 75%. Among woody species, A. marmelos exhibited comparatively lesser negative effect on growth and yield of B. campestris and T. aestivum than others. Distance from tree trunk affected growth and yield of both understory crops. Maximum yield was recorded at 4.5 m distance from tree trunk which decreased with decrease in the distance from tree base. Maximum decrease in yield of B. campestris and T. aestivum was noticed in close vicinity of tree-trunk (at 1.0 m). Between the two intercrops, reduction in the yield was more pronounced in B. campestris than T. aestivum. Remuneration to be generated from fruits and gum yields is likely to compensate reduction in the crop yields in near future and make this system viable for supporting livelihoods of marginal farmers in Bundelkhand region of Central India.